ASSESSMENT OF FINANCIAL DISTRESS USING THE ZMIJEWSKI METHOD: EVIDENCE FROM INDONESIA’S HEALTH SOCIAL SECURITY FUND - Reke, James Sylvanus Uly; Perangin-angin, Mori Agustina br (Distribusi - Journal of Management and Business, 2025)
This study analyses the financial condition of the National Health Insurance Program (JKN) in Indonesia, managed by BPJS Kesehatan, from 2020 to 2024 using the Zmijewski Method. Although membership coverage increased to 98.45% of the total population by 2024, the program showed fluctuating financial results, recording a surplus from 2020 to 2023 but expected to face a deficit in 2024 due to higher claims and operational costs. Zmijewski's method, which is applied through three financial ratios—Return on Assets (ROA), Debt-to-Asset Ratio (DAR), and Current Ratio (CR)—shows that although ROA continues to decline to a negative value in 2024, DAR has improved significantly, and CR indicates better liquidity. The X-Score value is consistently below zero, which means that BPJS Kesehatan is not in a state of financial distress. However, the movement of the X-Score close to zero indicates the potential for future vulnerabilities if a corrective strategy is not implemented.